ANALYSIS OF COMMUNICATION MANAGEMENT FACTORS ON THE LEVEL OF PROJECT SUCCESS (Case Study: Construction of North Sumatra Suspension Bridge) - Nabila Fitrah; Gina Cynthia Raphita Hasibuan; M. Ridwan Anas (Bulletin of Engineering Science, Technology and Industry, 2025)
Communication management plays a crucial role in ensuring the success of construction projects. This research aims to examine how communication management influences project success, taking the construction of the North Sumatra Suspension Bridge as a case study. The study utilizes the PLS-SEM method, with data gathered through surveys distributed to key stakeholders, including contractors, supervisory consultants, and the project owner. The findings reveal that the most significant communication management factors affecting project success are communication skills (0.917), contributing 10.39%; the use of tools and technology (0.904), contributing 10.25%; and communication frequency (0.901), contributing 10.21%. Overall, communication management accounts for 75.9% (R² = 0.759) of the variation in project success indicators. These results highlight a strong correlation between communication management components and project success in the North Sumatra Suspension Bridge. Implementing structured, technology-driven, and transparency-focused communication strategies can significantly enhance the effectiveness and efficiency of construction project execution.